Experiments and numerical simulations on damage behavior of biaxially loaded specimen. Issue 1 (December 2014) - Brenner, Daniel; Gerke, Steffen; Brünig, Michael
Abstract The paper deals with the effect of stress state on damage and failure behavior of isotropic ductile metals. In the continuum damage model the damage behavior of ductile metals is adequately described by a generalized damage condition and an anisotropic damage rule. The damage criterion is based on series of uniaxial experiments with differently notched specimens and corresponding numerical simulations as well as on various numerical calculations on the micro‐scale. Different branches of the damage criterion depending on stress triaxiality and Lode parameter are considered. To be able to validate the proposed stress‐state‐dependent functions new experiments with two‐dimensionally loaded specimens have been developed. Corresponding numerical simulations show that these shear‐tension and shear‐compression tests cover a wide range of stress triaxialities and Lode parameters. (© 2014 Wiley‐VCH Verlag GmbH & Co. KGaA, Weinheim)